Censuses in Slovakia in the interwar and post-war period - Tišliar, Pavol (Masaryk University Press, 2023)
The publication deals with individual census actions that took place in Slovakia in the interwar and post-war period. It analyses and evaluates the preparation, the course and partly evaluates the selected results of the censuses. One of the main objectives of the authors was to evaluate the quality of the results of census actions as a historical source. The publication is based primarily on archival research carried out in Slovak and Czech archives. In terms of the basic concept, the monograph is based on the publication P. Tišliar - B. Šprocha: Malé dejiny veľkých akcií : Sčítania ľudu a súpisové akcie na Slovensku v rokoch 1919 - 1950. Trnava: UCM, 2022, 350 s. ISBN 978-80-572-0267-7.